IMPROVING CREATIVE PERFORMANCE THROUGH OPPORTUNITY-ENHANCING HR PRACTICES: THE MEDIATION ROLE OF WORK ENGAGEMENT AND WORK-RELATED FLOW IN MANUFACTURING FIRM - Pasha Pingkaniswari; Unggul Kustiawan (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
This study aims to examine the influence of opportunity-enhancing HR practices on creative performance, by considering the mediating roles of work engagement and work related flow. A quantitative approach was applied using a survey method and CB-SEM SmartPLS analysis on 317 manufacturing employees in Tangerang. The results indicate that opportunity-enhancing HR practices has a significant positive effect on both creative performance and work engagement. Additionally, work autonomy and proactive personality significantly influence work engagement, while proactive personality also affects work related flow. Furthermore, work related flow mediates the relationship between proactive personality and creative performance. The study recommends that manufacturing firms implement policies that provide space for employee participation, creativity, and development initiatives. The primary contribution of this research is to strengthen the role of opportunity-enhancing HR practices for creative performance through optimal work engagement and work related flow. As well as to broaden theoretical understanding of the psychological dynamics of the manufacturing work environment.